MEASUREMENT OF ISO 9001:2008 IN PUSDATIN PUPR INDONESIA - Andini, Nurullina; Wella, Wella (Ultima Management : Jurnal Ilmu Manajemen, 2023)
Abstract - The issue at hand is to the implementation of the quality standard outlined in ISO 9001:2009, specifically focusing on clauses 4 through 8. In order to obtain the desired outcome, a comprehensive interview was conducted with the director of the department. Additionally, a total of 51 questionnaires were distributed among the 52 staff members, and relevant documents were carefully reviewed. The evaluation was conducted with the Likert Scale, and the final outcome was determined based on the maturity level. The implementation of clauses 4 to 8 of the ISO 9001:2008 quality standard at PUSDATIN has been successfully executed, achieving a level 4 rating (Managed and Measurable). PUSDATIN must enhance its capacity in order to attain the highest level of maturity, namely level 5. To get a level 5 rating, PUSDATIN should consider implementing ISO 9001:2008 standards. This would ensure that the required product quality is consistently maintained to meet customer expectations. Additionally, PUSDATIN can enhance its capabilities by recruiting professionals with expertise in quality management systems. Keywords: ISO 9001:2008; Maturity Level; Quality Management System; Quality Standard.